A new subspecies of Acrolejeunea arcuata, and notes on typification, synonymy, and distribution of other Australasian Lejeuneaceae - Renner, Matt A. M. (Phytotaxa, 2013)
Acrolejeunea arcuata subsp. gradsteinii is described for plants from the Wet Tropics of Queensland, Australia. This subspecies differs in its autoicy, oblong-elliptic underleaves, the female bract lobe not reflexed and with a rounded apex, and the second lobule tooth longer than the first. Ceratolejeunea belangeriana is confirmed for Australia on the basis of an early collection from Norfolk Island, and recent collections from Queensland. Lejeunea tumida is excluded from the flora of Australia, all Australian specimens identified as L. tumida are referable to other species. Lejeunea sordida is confirmed for Norfolk Island on the basis of material previously identified as L. tumida. Hygrolejeunea rostrata is lectotypified and moved from synonymy under L. discreta to synonymy under L. lumbricoides, which is newly reported for Australia from Norfolk Island. Hygrolejeunea norfolkensis is moved from synonymy under L. discreta to synonymy under L. gracilipes, which is newly recorded for Australia on this basis. A lectotype is proposed for Lejeunea helmsiana.